Primary Targeted Muscle Reinnervation after Below-Knee Amputation Is Not Associated with an Increased Risk of Major or Minor Surgical Complications: A Multi-Institutional, Propensity Score–Matched Analysis. Issue 3 (6th July 2022) - Shammas, Ronnie L.; Azoury, Said C.; Sergesketter, Amanda R.; Lee, Hui-Jie; Poehlein, Emily; Othman, Sammy E.; Cason, Roger W.; Levinson, Howard; Kovach, Stephen J.; Mithani, Suhail K.
Abstract : Background: Targeted muscle reinnervation has emerged as a technique to reduce neuroma and phantom limb pain after below-knee amputation; however, the incidence of postoperative complications remains unknown. This multi-institutional study assessed the risk of postoperative complications among patients who underwent targeted muscle reinnervation at the time of below-knee amputation. Methods: Patients who underwent below-knee amputation with targeted muscle reinnervation were propensity score–matched 1:3 to patients who underwent below-knee amputation alone. Study outcomes included the incidence of major or minor complications within 60 days. Regression models were used to estimate the relative risk of major and minor complications. Results: Overall, 96 patients were matched, including 31 patients who had below-knee amputation with targeted muscle reinnervation and 65 who had below-knee amputation alone. In the matched sample, a higher incidence of major complications (29 percent versus 24.6 percent), readmission (25.8 percent versus 18.5 percent), and reoperation (19.4 percent versus 10.8 percent) was seen after both procedures compared with below-knee amputation alone. Patients who underwent both procedures displayed a higher incidence of minor complications (25.8 percent versus 20.0 percent), blood transfusion (22.6 percent versus 18.5 percent), and wound healing complications (45.2 percent versus 33.8 percent) and longer operative time (mean ± SD, 188.5 ± 63.6 minutes versus 88 ± 28.2 minutes). There was no statistically significant difference in the risk of major (relative risk, 1.20; 90 percent CI, 0.68, 2.11) or minor (relative risk, 1.21; 90 percent CI, 0.61, 2.41) complications between the two cohorts. Conclusions: Despite an increased incidence of postoperative complications, undergoing below-knee amputation with targeted muscle reinnervation does not confer a statistically significant increased risk of major or minor complications. Future studies are needed to delineate patient selection criteria when assessing the suitability of targeted muscle reinnervation at the time of major limb amputation. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.